THE VOICE OF DEVOTION IN UZBEKISTAN POETRY - Rukhshona Ashirova (Лучшие интеллектуальные исследования, 2024)
Annotation: In this article, we will talk about Zulfiya Israilova, a famous and talented poet of the Uzbek people, a woman who valiantly fought for the place of Eastern women in society.